The pattern of mandibular third molar impaction and its relationship with the development of distal caries in adjacent second molars among Emiratis: a retrospective study - Mohammed Amjed Alsaegh; Dana Ayed Abushweme; Khadeija Othman Ahmed; Salhah Othman Ahmed (BMC, 2022)
Abstract Objectives The purpose of this study was to investigate the pattern of mandibular third molar (MTM) impaction and associated carious lesions in adjacent mandibular second molars (MSMs) in a sample of Emirati individuals. Methods This retrospective study assessed 2000 orthopantomograms of Emirati patients who visited the Specialized Fujairah Dental Center between 2015 and 2020. The depth, ramus relation and angulation of the impacted MTMs were assessed according to the Pell and Gregory classification and Winter's classification. In addition, carious lesions in adjacent MSMs associated with the evaluated parameters were identified. Results A total of 461 (23.05%) of the patients had at least one impacted MTM. The mean age of the study population was 26.24 years. Mesioangular, level B, and class II impactions were the most common, at 47.37% (χ2 = 382.134; p < 0.001), 45.48% (χ2 = 56.889; p < 0.001), and 74.05% (χ2 = 513.099; p < 0.001), respectively. There was a higher percentage of level C impaction among females than among males (χ2 = 19.178; p < 0.001). A total of 126 impacted teeth (18.36%) had associated carious lesions. These carious lesions were predominantly found in teeth with mesioangular impactions (χ2 = 59.430; p < 0.001), level A and B impactions (χ2 = 23.301; p < 0.001), and class II and I impactions (χ2 = 17.918; p = 0.006). Conclusions It is imperative to raise awareness of soft tissue mesioangular-impacted MTMs, as they are the most frequently associated with the development of carious lesions in adjacent MSMs. Approximately one quarter of evaluated Emiratis had at least one impacted MTM, with the most prevalent pattern being class II, level B, and mesioangular impactions. Furthermore, surgical removal is expected to be more challenging for females than for males.